Analisis Pengaruh Market Timing Terhadap Struktur Modal Perusahaan non-Keuangan yang Terdaftar di Bursa Efek Indonesia - Felicia Felicia; Ferdinand D. Saragih (Business Administration Department - Universitas Katolik Parahyangan, 2015)
The aim of this study is to analyze the persistence of the impact of market timing on capital structure of non-financial firms listed in Indonesia Stock Exchange. Market timing is measured from the perspective of IPO event, and divides the market into two sections, hot market and cold market. Firms that go public in hot market are identified as the market timers. From 93 sample data, the result shows that hot market-firms substantially issue more equity than cold market-firms do. Therefore, market timing has no impact on capital structure of non-financial firm in Indonesia, both in short-term and long-term. After going public, the impact of market timing vanished, which is indicated by the rise of the leverage level of hot market-firms in Indonesia. Keywords: Market timing, IPO, hot market and cold market, capital structure